Lipidomes of Icelandic bryophytes and screening of high contents of polyunsaturated fatty acids by using lipidomics approach. (February 2023) - Lu, Yi; Eiriksson, Finnur Freyr; Thorsteinsdóttir, Margrét; Cronberg, Nils; Simonsen, Henrik Toft
Abstract: Bryophytes (mosses, liverworts, and hornworts) have interested researchers because of their high chemical diversity and their potential uses in pharmaceutical, food, and cosmetic industries. Specifically, long-chain polyunsaturated fatty acids (l-PUFA) such as arachidonic acid (AA) and eicosapentaenoic acid (EPA) are commonly found in bryophytes, but not in vascular plants. Bryophytes accumulate PUFAs in cold or even freezing temperature to keep the cell fluidity. Iceland has a long history of bryophyte vegetation. These bryophytes are highly adapted to the harsh environment in Iceland and therefore are expected to produce high amounts of PUFAs. However, despite the fact that hundreds of mosses and liverworts have been found in Iceland, their lipid profiles largely remain unknown. In this study, we performed untargeted lipidomics by using UPLC-ESI-QTOF-MS as a rapid screening strategy to examine the lipid compositions of 39 local bryophyte species in Iceland and aimed to find high AA and EPA producers. A total of 280 lipid molecular species from 15 lipid classes were quantified with isotope-labeled internal standards. AA and EPA were abundantly distributed in the phospholipids (mainly PC and PE) and glycerolipids (MGDG and DGDG) in six moss species, namely Racomotrium lanuginosum, R. ericoides, Bryum psedotriquetrium, Plagiomnium ellipticum, Hylocomium splendens, and Rhytidiadelphus triquetrus . Two of the six species ( B. psedotriquetrium and H. splendens ) also accumulated high concentrations of PUFA-containing-triacylglycerols. Graphical abstract: Image 1 Highlights: Arachidonic acid (AA) and eicosapentaenoic acid (EPA) identified in at least 6 new bryophyte species. 280 lipid molecular species identified in 39 different Icelandic bryophyte species. The distribution of long-chain fatty acids is given.